How Do Observers Assess Resolve?. Issue 1 (13th January 2021) - Kertzer, Joshua D; Renshon, Jonathan; Yarhi-Milo, Keren
ABSTRACT: Despite a plethora of theoretical frameworks, IR scholars have struggled with the question of how observers assess resolve. We make two important contributions in this direction. Conceptually, we develop an integrative framework that unites otherwise disconnected theories, viewing them as a set of heuristics actors use to simplify information-rich environments. Methodologically, we employ a conjoint experiment that provides empirical traction impossible to obtain using alternative research designs. We find that ordinary citizens are 'intuitive deterrence theorists' who focus to a great extent on capabilities, stakes, signals and past actions in judging resolve. We also find that observers see democracies as less resolved than autocracies (not more), casting doubt on key propositions of democratic credibility theory. Finally, a conceptual replication shows that a group of elite decision makers converge with the US public in how they interpret costly signals, and in viewing democracies as less resolved than autocracies.